Navigation Did Not Improve the Precision of Minimally Invasive Knee Arthroplasty - Bonutti, Peter M. (Springer-Verlag, 2008)
Potential advantages of minimally invasive total knee arthroplasty (TKA) include decreased pain, faster recovery, and increased quadriceps muscle strength. Computer-assisted navigation has been associated with more accurate component alignment. We evaluated two groups of 50 patients who had minimally invasive TKAs performed with and without navigation by two surgeons. A comparison of 50 previous TKAs by each of the two surgeons showed similar results. The mean operative times for the navigation and nonnavigation groups were 112 minutes (range, 63–297 minutes) and 54 minutes (range, 35–86 minutes), respectively. The mean estimated blood losses, mean Knee Society pain as well as functional scores and mean component alignments were similar. The number of knees that deviated by more than 3° from the normal anatomic axis was three and one in the navigated and nonnavigated groups, respectively. Complication rates were 6% and 4% in the navigated and nonnavigated groups, respectively. Our data demonstrate no distinct advantage of navigation when combined with a minimally invasive approach. Level of Evidence: Level II, therapeutic study. See the Guidelines for Authors for a complete description of levels of evidence.